The influence of haptics when assessing household products presented in different means: a comparative study in real setting, flat display, and virtual reality environments with and without passive haptics. Issue 1 (15th December 2020) - Galán, Julia; Felip, Francisco; García-García, Carlos; Contero, Manuel
Abstract: This research aimed to analyse the influence of presentation means in assessing different household product characteristics and to study the influence of physical contact with the product on that assessment. To this end, the presentation of an armchair in four different means was prepared: two offering the chance to touch the product (real setting and virtual reality with passive haptics) and two not offering the physical interaction possibility (virtual reality and 3D interactive image on a screen). The product was assessed by 128 volunteers (74 men, 54 women) on a semantic scale with 12 bipolar pairs. The results revealed that the presentation means did not influence the overall product assessment, but affected the assessment of 3 of 12 features (weight, size, and aesthetics), where coming into physical contact with the product impacted the assessment of these features. Finally, similar assessments of the product were obtained in both means of visual-only presentation. Graphical Abstract: